2021
DOI: 10.2217/pme-2020-0185
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ Knowledge, Attitudes and Future Expectations Towards Personalized Medicine

Abstract: Aim: Personalized medicine (PM) is a novel approach to diagnose and treat disease. The study assessed the knowledge, attitudes and future expectations of healthcare professionals (HPs) towards PM in Ethiopia. Materials & methods: A cross-sectional survey with primary data and a simple random sampling technique was applied to collect data. Results: Our study revealed from a total of 384 respondents, 98 (25.5%), 146 (38%) and 140 (36.5%) had good, medium and poor knowledge of PM, respectively. However, 172 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…Also, another previous study found that students with science majors outperformed non-science majors in genetic learning [ 21 ], which might also explain the attitude and feeling well informed about PM among students in the two majors. Another study conducted among healthcare professionals also confirmed that limited knowledge and negative attitudes were associated with a lack of awareness of PM [ 22 ], which also corresponded to our results. Our survey found that most students were “not too much” informed about PM.…”
Section: Discussionsupporting
confidence: 91%
“…Also, another previous study found that students with science majors outperformed non-science majors in genetic learning [ 21 ], which might also explain the attitude and feeling well informed about PM among students in the two majors. Another study conducted among healthcare professionals also confirmed that limited knowledge and negative attitudes were associated with a lack of awareness of PM [ 22 ], which also corresponded to our results. Our survey found that most students were “not too much” informed about PM.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, there were few studies on the potential risk factors of refractory peritonitis, and there were no studies to establish a visual prediction model after identifying the risk factors, which makes clinicians lack an intuitive and practical tool for individualized prediction of the occurrence of refractory peritonitis. With the advancement of medical technology, personalized medicine, which means tailoring treatment plans for individual patients, is receiving increasing attention [ 8 ]. Therefore, this study aims to identify the potential risk factors of refractory peritonitis and construct a nomogram to personalize clinical decision-making, improve patient care, and enhance the quality of peritonitis treatment.…”
Section: Introductionmentioning
confidence: 99%